Global rangelands data platform - Flintan, Fiona E.; Getahun, Yasin; Garcia, Carlos Domenech (CGIAR System Organization, 2024)
A global platform for multiple users including the UN and other development agencies for sourcing, consolidating, and sharing information on rangelands status, change, influencing forces, and restoration opportunities.